CATARACTA NIGRA (BLACK CATARACT): A CHALLENGING TASK MADE EASY WITH SUTURELESS MANUAL EXTRACAPSULAR CATARACT EXTRACTION - Zaman, Mir; Qadir, Afzal; Maooz, Maooz; Shah, Irfanullah; Rehman, Ishfaq -ur-; Babar, Tariq Farooq (Journal of Ayub Medical College Abbottabad, 2011)
Background: Cataract surgery is constantly evolving and various procedures having their merits and demerits are practiced by ophthalmologists all over the world. The objective of this study was to evaluate the safety, efficacy, visual outcome and complications of sutureless manual extracapsular cataract extraction (SMECE) in the management of patients with black cataracts using envelop anterior capsulotomy and soft shell technique. Methods: In a prospective observational study conducted at Khyber Institute of Ophthalmic Medical Sciences, Hayatabad Medical Complex, from January 2008 to December 2009, a total of 125 consecutive patients with black cataract underwent cataract extraction using SMECE with an envelop or V-type anterior capsulotomy and soft shell technique. Their operative, postoperative complications, visual outcome and efficacy were analysed. Results: Of 125 eyes with black cataracts SMECE was performed through a 12 O'clock sclerocorneal tunnel. The main Intraoperative complication was hyphaema in 10 (8%) patients. Postoperatively 9 (7.2%) patients had hyphaema. Fifteen (12%) eyes had some amount of striate keratitis superiorly. Twenty (16%) of patients had mild iritis. On 6th week follow-up 100 (80%) patients achieved uncorrected visual acuity of 6/6 to 6/18. Conclusion: SMECE with envelop or V-type anterior capsulotomy and soft shell technique is a safe and effective technique of cataract extraction in Cataracta Nigra (black cataract). Keywords: Cataracta Nigra, sutureless/extracapsular cataract extraction, SMECE, visual outcome